Dietary intake of antioxidants in patients with myelodysplastic syndrome - Rodrigues, Ana Raquel Eugênio Costa; Sales, Andressa Eslayne Caldas; Pinheiro, Helen; Barros, Gustavo André Bandeira do Rêgo; Lopes, Synara Cavalcante; Alexandrino, Renata Kellen Cavalcante; Melo, Priscilla Taumaturgo Holanda; Leite, Lília Teixeira Eufrásio; Sousa, Vivian Braga Gomes de; Mendonça, Priscila da Silva (Seven Editora, 2023)
Introduction: Changes in lifestyle, including eating habits, are determining factors in the possibility of protecting the body against the development of neoplastic tumors, including Myelodysplastic Syndrome (MDS). Objectives: To evaluate the usual intake of antioxidants in patients diagnosed with MDS. Methods: Cross-sectional study in a tertiary university hospital in Ceará. Participants were 102 patients with MDS and 102 healthy individuals, matched according to sex and age. Food consumption was evaluated through 2 24-hour recordings, and the nutritional orientation of the intake of antioxidant micronutrients (vitamins A, C and E and the minerals zinc, selenium and magnesium) was analyzed. Results: Most participants were female (62.7%). The mean age of patients with MDS was 72.07 years ± 11.63 and of controls was 69.24 ± 9.24 (p= 0.066). Among the MDS group, 77.5% were aged 65 years or older. The nutrients with the highest prevalence of inadequacy among patients with DMS were selenium (100.0%) and magnesium (98.0%). There was no difference in the prevalence of inadequate consumption of vitamin A, C, E, magnesium, selenium and zinc between the group with MDS and controls (p> 0.05). Patients with MDS older than 65 years had significantly lower consumption of vitamin C (p= 0.037) and selenium (p= 0.004) than the group of young patients. Conclusion: The study showed a high prevalence of inadequate consumption of antioxidant vitamins and minerals among patients with MDS and a healthy population, with emphasis on the lower intake of vitamin C and selenium associated with the group with MDS aged over 65 years. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-067